Digitalisation of Teaching Materials for Toba Batak Ethnic Decorative Variety with Procreate Media Based on p-Books and e-Books - Adek Cerah Kurnia Azis; Siti Khodijah Lubis; Gamal Kartono; Muhammad Anggie Januarsyah Daulay (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This research aims to develop teaching materials in the form of digitalisation of Toba Batak Ethnic Decorative Variety with p-book and e-book-based procreate media that are valid, practical, and effective in the Fine Arts Department. This research method uses research and development with the 4-D development model (Four-D Models), namely define, design, develop, and disseminate. This research instrument uses a questionnaire with a Likert scale, while the data analysis technique consists of analysing the validity, practicality and effectiveness of teaching materials. The results of this study indicate that: a) p-book and e-book-based teaching materials with the title of the book/module/teaching material